Transitioning from Block-Based to Text-Based Programming Languages - Moors, Luke; Luxton-Reilly, Andrew; Denny, Paul (Proceedings (Learning and Teaching in Computing and Engineering. Online), 2018)
Block-based programming environments are becoming increasingly popular as introductory tools for teaching programming to children. These environments differ significantly from their text-based counterparts and have proven to be successful in motivating children and making it easy to start programming. However, several studies have recognised drawbacks of these tools which could potentially be detrimental when students transition to text-based languages. In this paper, the distinguishing features between block-based environments and text-based languages are discussed and the effectiveness of these features are explained. In considering the transition to text-based languages, this paper identifies two significant weaknesses to block-based programming and discusses suggestions for improvement.